Peningkatan Literasi Keagaamaan Kelompok Remaja Masjid Ihtimam sebagai Upaya Preventif Perilaku Intoleransi Beragama: Increasing Religious Literacy of Youth Group of Ihtimam Mosque as a Preventive Effort for Religious Intolerance Behavior - Ghufronudin Ghufronudin; Bagas Narendra Parahita; Anis Suryaningsih; Yuhastina Yuhastina; Aris Arif Mundayat (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Adolescents' participation in a religious community can influence the formation of patterns of social interaction in their environment. Ihtimam Mosque Community Youth (REKOMAS) is a youth religious organization that focuses on mosque activities for the community around the mosque's location. The existence of youth in the mosque community has had many positive impacts on the community, especially in providing facilities for social, educational, and religious activities. In the organizational process, they must gain new knowledge about religious literacy to strengthen the members' mentality. Therefore, this service activity is carried out to increase the capacity of youth religious literacy as a preventive effort to overcome intolerant behavior. Technically, implementing community service activities is carried out through informal sharing activities discussing various contextual problems experienced by most members. The selection of problem topics was chosen based on the closeness of the topic to the members and the interest of the topic for discussion through a social and religious perspective approach. Through this activity, it is hoped that it will be able to increase the capacity of religious literacy to overcome the behavior of religious intolerance in society.